2005
DOI: 10.1177/107179190501100302
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity and Leadership in the Basque Region: A Study of Leadership Development Programmes

Abstract: The purpose of the study was to explore how social identity influences the construction of leadership development programmes in the Basque Region. The Basque region is recognised as having a strong social and national identity (Kaufmann and Tödtling, 2000; McNeill, 2000). Historically leadership development has been focused on practising leaders and managers and delivered by universities, consultants and other intermediaries. A recent study reported in the paper has shown managerial dissatisfaction with curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…They argued that student leaders from different cultural backgrounds might have different expectations regarding leader performance or personality. Consistently, Pittaway et al, (2005) noted that leadership was sensitive to culture. The results from this study suggest that Mexican and Spanish undergraduate students perceive leadership behavior differently.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They argued that student leaders from different cultural backgrounds might have different expectations regarding leader performance or personality. Consistently, Pittaway et al, (2005) noted that leadership was sensitive to culture. The results from this study suggest that Mexican and Spanish undergraduate students perceive leadership behavior differently.…”
Section: Discussionmentioning
confidence: 83%
“…Like entrepreneurship, the concept of leadership, and therefore leadership programs, are sensitive to cultural differences (Pittaway, Rivera, & Murphy, 2005). This raises the question of the role of faculty members from different parts of the world in identifying the appropriate leadership model for their students, given their cultural background.…”
Section: Culture Assessment and Self-efficacymentioning
confidence: 99%
“…Management and leadership theories and development practices come out and make sense in a specific time and place, linked to personal issues concerning identity (Pittaway, Rivera & Murphy, 2005). Thus, to truly understand management development, programs should be constructed within the boundaries of personal experience and identity.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Recent studies on leadership (Rousseau and van der Veen, 2001;Pittaway et al, 2003;Andras and Charlton, 2005;Mullern and Wahlin, 2005) have shown a great interest in identity construction among leaders and managers of organizations. The focus of these studies is on the changing organizational settings and the pressure that has been put on the leaders and managers to re-construct their identities and re-define their roles in order to cope with the structural demands of the organizations.…”
Section: Identity Theoriesmentioning
confidence: 99%
“…Identification is a process, in identity theory, whereby symbols are used to designate positions to the individuals in a group or institutions. People who hold positions in the social structure of a particular organization are given names according to the roles which they occupy or perform (Pittaway et al, 2003). Principals of schools construct professional identities of themselves based on the meanings and expectations of their role as leaders.…”
Section: Constructing Professional Identitymentioning
confidence: 99%